The Argentine Universities in the Context of Policies of the 90s: The Case of the Joint Degree in Science Education UNICEN - Richmond, Iris (Education Policy Analysis Archives, 2006)
This article analyses the changes caused by the implementation of an articulated degree in Educational Sciences at the Universidad Nacional at Centro de la Provincia in Buenos Aires (Argentina). This educational program should be understood within the framework provided by the structural reforms of the educational system, promoted by the national government in the 1990's with the intention of restructuring the State–Society relations. This program that appeared to be promoting the democratization of access to the university system was transformed into a market mechanism, for the provision of financial resources to the university by selling "knowledge" to graduates from teacher education programs.